Common Factors of Alzheimer’s Disease and Rheumatoid Arthritis—Pathomechanism and Treatment - Paulina Trzeciak; Mariola Herbet; Jarosław Dudka (Molecules, 2021)
The accumulation of amyloid plaques, or misfolded fragments of proteins, leads to the development of a condition known as amyloidosis, which is clinically recognized as a systemic disease. Amyloidosis plays a special role in the pathogenesis of neurodegenerative diseases such as Alzheimer’s disease (AD), Parkinson’s disease, and rheumatoid arthritis (RA). The occurrence of amyloidosis correlates with the aging process of the organism, and since nowadays, old age is determined by the comfort of functioning and the elimination of unpleasant disease symptoms in the elderly, exposure to this subject is justified. In Alzheimer’s disease, amyloid plaques negatively affect glutaminergic and cholinergic transmission and loss of sympathetic protein, while in RA, amyloids stimulated by the activity of the immune system affect the degradation of the osteoarticular bond. The following monograph draws attention to the over-reactivity of the immune system in AD and RA, describes the functionality of the blood–brain barrier as an intermediary medium between RA and AD, and indicates the direction of research to date, focusing on determining the relationship and the cause–effect link between these disorders. The paper presents possible directions for the treatment of amyloidosis, with particular emphasis on innovative therapies.